The diversity of useful plants and botanical knowledge of the Rejang Tribe in Kepahiang District, Bengkulu Province, Indonesia - WIRYONO WIRYONO; Sriwahyuni; Gusti Ayu Winanda; Saprinurdin; Steffanie Nurliana (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Wiryono, Sriwahyuni, Winanda GA, Saprinurdin, Nurliana S. 2019. The diversity of useful plants and botanical knowledge of the Rejang Tribe in Kepahiang District, Bengkulu Province, Indonesia. Biodiversitas 20: 3599-3607. The rural people derive multiple benefits from the highly diverse plants in their traditional gardens and the nearby natural forests. However, the conversion of natural forests and traditional gardens into monoculture plantations in many areas has reduced the plant diversity, which in turn has also reduced the botanical knowledge, especially among the younger generation. This study was conducted to know: (i) the diversity of plant species used by the people of Rejang tribe in Kota Agung Village, Kepahiang District, Bengkulu Province, Indonesia, (ii) the correlation between age and botanical knowledge, and (iii) the effect of gender on the botanical knowledge. Data were collected through interviews with five key informants and 68 villagers, and the data were analyzed qualitatively and quantitatively using t-test and regression analyses. The results showed that the Rejang people in Kota Agung Village used 130 plant species for 12 different purposes. The three top use categories were food, medicine, and ornament. The botanical knowledge was positively correlated with age, and women had better botanical knowledge than men, presumably due to the longer time they spend in taking care of the homegardens. This study confirms the worldwide trend that there is a decline in botanical knowledge among young people.